Alluring Monsters: The Pontianak and Cinemas of Decolonization, Rosalind Galt (2021). Issue 1 (7th March 2023) - Mather, Philippe
Review of: Alluring Monsters: The Pontianak and Cinemas of Decolonization, Rosalind Galt (2021) New York: Columbia University Press, 312 pp., ISBN 978-0-23120-133-9, p/bk, 35.00